Fast handover scheme based on redundant router information and pre-buffering strategy for mobile IPv6 - TANG Jun; PEI Chang-xing; SU Bo (Tongxin xuebao)
The issue of IP connectivity resumption in case of erroneous prediction was investigated in fast handovers for IPv6（FMIPv6） protocol.Based on the redundant router information and pre-buffering strategy,a new scheme called RIRS（router information redundancy scheme） was proposed.The scheme constructed redundant router table for handover in order to assist the mobile node to re-formulate a new care of address quickly,and employed pre-buffering strategy to protect the packets destined for mobile node during handover.Simulation results indicate that RIRS can achieve better performance in terms of handover latency and packet loss compared with FMIPv6.